The Regional Research And Development Centre of the Asean Institute of Technology, Bangkok - anonymous anonymous (Universitas Gadjah Mada, 1986)
The Asian Institure of Technology (AJT) is an autonomouse, International postgraduate Institute. It provides advanced education in engenering, science and allied fields through academic programme loading to Master's and Doctoral degree and Diplomat, and through research programmes are related closely to the needs of Asia.